Combined uranium-series and electron spin resonance dating from the Pliocene fossil sites of Aves and Milo’s palaeocaves, Bolt’s Farm, Cradle of Humankind, South Africa - Yu,Wenjing; Herries,Andy I. R.; Edwards,Tara; Armstrong,Brian; Joannes-Boyau,Renaud (PeerJ, 2024)
Bolt’s Farm is the name given to a series of non-hominin bearing fossil sites that have often been suggested to be some of the oldest Pliocene sites in the Cradle of Humankind, South Africa. This article reports the results of the first combined Uranium-Series and Electron Spin Resonance (US-ESR) dating of bovid teeth at Milo’s Cave and Aves Cave at Bolt’s Farm. Both tooth enamel fragments and tooth enamel powder ages were presented for comparison. US-ESR, EU and LU models are calculated. Overall, the powder ages are consistent with previous uranium-lead and palaeomagnetic age estimates for the Aves Cave deposit, which suggest an age between ~3.15 and 2.61 Ma and provide the first ages for Milo’s Cave dates to between ~3.1 and 2.7 Ma. The final ages were not overly dependent on the models used (US-ESR, LU or EU), which all overlap within error. These ages are all consistent with the biochronological age estimate (<3.4–>2.6 Ma) based on the occurrence of Stage I Metridiochoerus andrewsi. Preliminary palaeomagnetic analysis from Milo’s Cave indicates a reversal takes place at the site with predominantly intermediate directions, suggesting the deposit may date to the period between ~3.03 and 3.11 Ma within error of the ESR ages. This further suggests that there are no definitive examples of palaeocave deposits at Bolt’s Farm older than 3.2 Ma. This research indicates that US-ESR dating has the potential to date fossil sites in the Cradle of Humankind to over 3 Ma. However, bulk sample analysis for US-ESR dating is recommended for sites over 3 Ma.
Keywords: Combined US-ESR dating; Fossil teeth; Bolt’s Farm; Pliocene; Pleistocene; Palaeocave; Geochronology; Direct dating; South African fossils; Palaeomagnetism